Strategi Pemasaran Usaha Art Shop Lokal Dalam Menghadapi Persaingan Global Di Lingkungan Batu Belig, Kelurahan Kerobokan Kelod, Kabupaten Badung - Purnamasari, Kadek Ayu; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p04, 2018)
This study aims to determine the marketing strategy for the local art shops at Batu Belig, Badung Regency. This research is interesting to be conducted because there is a difference between local and foreign art shops which could be identified from several aspects. This research is both interesting as well as important to make the local peoples as locals entrepreneurs  to be able to compete with the investors. The data in this study are qualitative data, which were obtained based on the results of observation, in- depth interviews, literature studies, and questionnaires. The amount of sampling is 60 respondents and they were selected using purposive and accidental sampling. In  order to survive in this tourism business, local owners must have a marketing strategy to increase the promotion by introducing Balinese culture, creat the innovative design of new product, making corporate identity, and increasing market segmentation,  the positive image, product quality and the quality of service. The suggestion in this study is local entrepreneurs should be able to create some innovative products that are more representing  Balinese culture.   Keywords: art shop, strategy, Balinese culture